2016
DOI: 10.1007/s00425-016-2638-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of proanthocyanidins and/or lignin deposition in buff-pigmented soybean seed coats may lead to frequent defective cracking

Abstract: Defective cracking frequently occurs in buff-pigmented soybean seed coats, where proanthocyanidins accumulate and lignin is deposited, suggesting that proanthocyanidins and/or lignin may change physical properties and lead to defective cracking. In the seed production of many yellow soybean (Glycine max) cultivars, very low percentages of self-pigmented seeds are commonly found. This phenomenon is derived from a recessive mutation of the I gene inhibiting seed coat pigmentation. In Japan, most of these self-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Despite this, few analytical progresses have been reported. Senda et al (2017) suggested that proanthocyanidins and lignin are related to the SCC of buff-pigmented soybean seeds. Percy et al (1999) reported that soluble proline-rich cell wall protein is absent in net-like seed-coat-defective soybean lines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, few analytical progresses have been reported. Senda et al (2017) suggested that proanthocyanidins and lignin are related to the SCC of buff-pigmented soybean seeds. Percy et al (1999) reported that soluble proline-rich cell wall protein is absent in net-like seed-coat-defective soybean lines.…”
Section: Discussionmentioning
confidence: 99%
“…Since procyanidins B are mostly catechin dimers, these compounds, previously identified in the seed and seed coats of lentil, pardina lentil, pea and common bean were assigned as procyanidin B1 and procyanidin B2 because of the MS 2 fragment ion [M-H] − at m/z 289 which is characteristic of catechin monomer (49). The presence of procyanidin type B dimers has been described in seeds of most grain legumes, and their synthesis may depend on the legume's phenotype (50,51). Moreover, B-type procyanidin trimers which were found in the test landraces were earlier detected in the seeds of cowpea, adzuki bean, pea and lentil (4,49).…”
Section: Flavonoids In Seeds Of the Orphan Kersting's Groundnutmentioning
confidence: 99%
“…Anatomical characterization showed the rupture and compression of the hourglass cells (second cell layer of the seed coat) that act to softening the effects of expansion, contraction, and rupture of the parenchyma cells when subjected to subsequent hydration and dehydration cycles (Forti et al, 2013;Senda et al, 2017). Therefore, cotyledonary cells of the seeds under simulated precipitation were more exposed to environmental conditions, and their deterioration process increased, which was reinforced by the results of the physiological and X-ray tests.…”
Section: Discussionmentioning
confidence: 99%